OBSERVATIONS ON THE FLUCTUATIONS IN PROTEIN, FAT AND WATER CONTENT IN CYPRINUS CARPIO (LINN.) IN RELATION TO THE STAGES OF MATURITY - Masurekar, V B; Pai, S R (Indian Journal of Fisheries, 2011)
The muscles of the freshwater fish, Cyprinus carpio were analysed for their protein, fat and water content over a period in which the different maturity stages of the fish weire obtained. The variations in the above mentioned body constituents were seen to be related to the reiproduction cycle. A gradual depletion was observed during maturation, and the least prote.’n and fat content was observed in the spent individuals. Variations were also found in the serum protein patterns in the female in different matudty stages as demonstrated by polyacrylamide electrophoresis.